American Prints 1913-1963 - Castelman, Riva; Koninklijke Bibliothek Albert I, Brussel (Brussel : Koninklijke Bibliotheek Albert I Brussel, 1976)
Albers, Josef ; Albright, Ivan Le Lorraine ; Antreasian, Garo Zareh ; Arms, John Taylor ; Barnet, Will ; Baskin, Leonard ; Bellows, George ; Benton, Thomas Hart ; Bertola, Harry ; Bontecou, Lee ; Bourgeois, Louise ; Cadmus, Paul ; Calder, Alexander ; Castellon, Federico ; Crawford, Ralston ; Curry, John Steuart ; Davies, Arthur B. ; Davis, Stuart ; Dine, Jim ; Feininger, Lyonel ; Forsberg, James ; Francis, Sam ; Frankenthaler, Helen ; Frasconi, Antonio ; Gabo, Naum ; Glarner, Fritz ; Gorky, Arshile ; Gropper, William ; Gwathmey, Robert ; Hart, George "Pop" ; Hassam, Childe ; Hopper, Edward ; Hunt, Richard ; Johns, Jasper ; Jones, John Paul ; Jordan, Raymond ; Kent, Rockwell ; Kline, Franz ; Kohn, Misch ; de Kooning, Willem ; Kuhn, Walt ; Kuniyoshi, Yasuo ; Landacre, Paul ; Landeck, Armin ; Lasansky, Mauricio ; Lebrun, Rico ; Lewis, Martin ; Liberman, Alexander ; Lozowick, Louis ; Margo, Boris ; Marin, John ; Marsh, Reginald ; Matulka, Jan ; Mazur, Michael ; McGarrell, James ; Motherwell, Robert ; Nadelman, Elie ; Nevelson, Louise ; Newman, Barnett ; Oldenburg, Claes ; Pennell, Joseph ; Peterdi, Gabor ; Pollock, Jackson ; Racz, André ; Rauschenberg, Robert ; Reder, Bernard ; Riggs, Robert ; Rivers, Larry ; Schanker, Louis ; Schrag, Karl ; Seligmann, Kurt ; Shahn, Ben ; Sheeler, Charles ; Sloan, John ; Soyer, Raphael ; Spencer, Niles ; Summers, Carol ; Tanguy, Yves ; Tanning, Dorothea ; Wald, Sylvia ; Wayne, June ; Weber, Max ; Wood, Grant ; Yunkers, Adja ; Zorach, William
Engels
American Prints 1913-1963, Koninklijke Bibliotheek Albert I Brussel, 27.3 - 8.5.1976
boek
Keywords: Amerika